Justifying Designation and the Unified Linkage of Etymology between the Signifier and its Signified according to Ibn Atheer’s Alnihayat Fi Gharib Al-Hadith and Al-Athar - Tawfiq Ali, Maha Jassim; Ahmed, Fadel Abd (Journal of Tikrit University for Humanities, 2023)
The book alnihayat fi Gharib Al-Hadith and Al-Athar by Imam Ibn Al-Atheer Al-Jazari is one of the most important works of the sixth century AH, which contributed to the service of the Arabic language in general, and the noble hadith in particular. To clarify a large number of strange words, justify their name, and understand the reasons for the names for which they are used, and by which the words multiply, and take different meanings, this search tackles the explanation of the naming and the unity of the etymological link between the noun and itself. The research is divided into six parts: the derivation of the naming from its signified, the derivation of the naming from the adjective or description, the derivation of the naming from the shape, the derivation of the naming from the verb, the derivation of the name from the sound, and the derivation of the name from the color. The research concludes that the word is not strange in the known sense, but rather derived from the original language. It has become strange, however, because of its seldom use, and its different pronunciation which is related to the fact that hadiths were narrated with different meanings by means of different languages, namely of the Arabs and non-Arabs at the advent of Islam.